GENDER INJUSTICE IN THE NOVEL BASIRAH BY YETTI A.KA GENDER INJUSTICE IN THE NOVEL BASIRAH BY YETTI A.KA - Septia, Emil; Yusandra, Titiek Fujita; Yolanda, Meriska (ppjbsip, 2021)
This study is motivated by the existence of several gender inequalities in Yetti A. KA's novel. This study focuses on the forms and factors that cause gender inequality. The purpose of this study is to describe the forms and factors that cause gender inequality. The method used in this qualitative research is descriptive. The data source used is the novel by Yetti A. KA. Based on the research conducted, the data obtained in the form of gender inequality in the novel Basirah consists of subordination, stereotypes, violence, and workload. The factors causing gender inequality in the novel consist of myths that have been passed down from generation to generation in society, patriarchal culture, and the prevailing capitalist system. The most dominant form of gender injustice found in the novel Basirah is violence. Meanwhile, the most dominant causative factor in gender inequality found is patriarchal Â AbstrakPenelitian ini adalah penelitian kualitatif dengan menggunakan metode deskriptif analisis. Data dalam penelitian ini berupa kata, kalimat yang berhubungan dengan ketidakadilan gender. Sumber data dalam penelitian ini adalah novel Basirah karya Yetti A.KA. Berdasarkan hasil penelitian, maka diperoleh data bentuk-bentuk ketidakadilan gender dalam novel Basirah karya Yetti A.KA, yang terdiri dari subordinasi, stereotipe, kekerasan (violence), dan beban kerja. Pada faktor penyebab ketidakadilan gender dalam novel Basirah karya Yetti A.KA terdiri dari mitos yang berlangsung turun temurun di masyarakat, budaya patriarki, dan sistem kapitalis yang berlaku. Bentuk-bentuk ketidakadilan gender yang paling dominan ditemukan dalam novel Basirah karya Yetti A.KA adalah bentuk kekerasan. Dan faktor penyebab dalam ketidakadilan gender yang paling dominan ditemukan dalam novel Basirah karya Yetti A.KA adalah budaya patriarki.